Recycling Antibiotics into GUMBOS: A Novel Approach to Address Multi-Drug-Resistant Bacteria - Bakare-Abidola, Taiwo; Adisa, Ayobami; Olaoye, Jelil (Mikailalsys Journal of Advanced Engineering International, 2025)
Antimicrobial resistance (AMR) represents one of the most critical global health challenges, as multidrug-resistant (MDR) pathogens continue to rise, threatening the efficacy of conventional antibiotics. To combat this growing threat, innovative approaches, such as the recycling of antibiotics into Group of Uniform Materials Based on Organic Salts (GUMBOS), have emerged. GUMBOS are a novel class of compounds formed by combining antibiotics with counter-ions to modify their physicochemical properties, leading to enhanced antimicrobial activity, stability, and bioactivity. This review explores the design, mechanisms of action, and applications of GUMBOS, highlighting their potential in overcoming resistance, improving drug delivery, and offering new therapeutic options. The review also discusses the challenges and limitations, including toxicity concerns, scale-up difficulties, and regulatory hurdles. Furthermore, it emphasizes future perspectives, including the integration of GUMBOS with nanotechnology and their potential as a platform for broader drug repurposing. Although promising, the successful clinical translation of GUMBOS will require extensive in vivo studies and clinical trials to confirm their safety and efficacy. This approach not only presents a sustainable solution to AMR but also opens new avenues for the innovative delivery of therapeutic agents.